액화수소 저장탱크의 수평요동이 증발 특성에 미치는 영향에 대한 연구 - 오승준(SEUNG JUN OH); 권준영(JUN YEONG KWON); 윤정환(JEONG HWAN YOON) (한국수소 및 신에너지학회 논문집, 2023)
Recently, a study on alternative and renewable energy is being conducted due to energy depletion and environmental problems. In particular, a hydrogen has the advantage of converting and storing the remaining energy into water-electrolyzed hydrogen through renewable energy generation. In general, due to reasons such as insulation problems, a study on high-pressure hydrogen storage tanks and related parts has recently been conducted. However, in the case of liquid hydrogen, the volume can be reduced by about 800 times or more compared to high-pressure hydrogen gas, so the study on this is needed as a technology that can increase energy density. In this study, the evaporation characteristics were analyzed under fixed heat flux conditions for liquid hydrogen storage tanks and the change in thermal stratification according to sloshing was analyzed. The heat flux condition was fixed at 250 W/m2 and the horizontal resonance frequency of the primary mode was applied to the storage tank. As a result, it was confirmed that the thermal stratification phenomenon decreased compared to the case where the slashing was not present due to forced convection when the slashing was present.